Do paradigma essencialista para o pós-estruturalismo: uma reflexão epistemológica sobre sexualidade - Pinafi, Tânia [UNESP] (Associacao Brasileira de Psicologia, 2015)
In this paper, we seek to develop an epistemological analysis of the normalization of sexuality based on an antithetical model- normal vs. abject, in terms of historical, psychological and sociological circumstances. Furthermore, we are interested in exploring the contributions of queer theory in relation to the thinking of sexuality. Keeping this in mind, our focus lies on two main areas. First, on an epistemological model based upon the universal subjects in human sciences that defined certain kind of sex/gender discrimination. Secondly, we search for theoretical formulations that expose the natural form in which we label certain existences as abject, and through this, try to construct a way of fighting existing homophobia in our society. Finally, the key aspect of the current discussion relies in the theoretical knowledges that can be used to better comprehend the performative capacity of subjects that live beyond the boundaries of heterosexuality. Taking this into account, now as in the past, psychology cannot ignore social events, having to consider not only the interiority of subjects, but also the social, historical and cultural environments that surround their lives.
From the esencialist paradigm to post- structuralism: An epistemological analysis regarding sexuality
Keywords: Epistemology; Queer; Sexuality